Alleviation of Moral Disgust, Shame, and Guilt in Posttraumatic Stress Reactions: An Evaluation of Comprehensive Distancing. (November 2014) - Ojserkis, Rachel; McKay, Dean; Badour, Christal L.; Feldner, Matthew T.; Arocho, Justin; Dutton, Courtney
Research suggests that moral disgust, shame, and guilt are present in posttraumatic psychopathology. However, it is unclear that these emotional states are responsive to empirically supported interventions for posttraumatic stress symptoms (PTSS). This study explored the relations among moral disgust, shame, guilt, and PTSS, and examined comprehensive distancing (CD) as a novel intervention for these emotional states in undergraduates with elevated PTSS. Participants were randomly assigned to use a CD or a cognitive challenge task in response to personalized scripts of a traumatic event. Both interventions were associated with decreases in disgust, moral disgust, shame, and guilt. Contrary to predictions, there were no significant differences between the exercises in the reduction of negative emotions. In addition, PTSS severity was correlated with trauma-related guilt as well as state guilt and shame, but not trait or state measures of disgust or moral disgust. This proof of concept project sets the stage for further research examining CD as an alternative or adjunctive intervention for posttraumatic stress reactions with strong features of moral disgust, shame, and guilt.